THE EFFECT OF GLYCEMIC INDEX ON PLASMA IL-6 IN SUB-MAX EXERCISE - S.H. Hasani; S. Supaporn; A.B. Mehranpour; M. Witid (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: This study examined the effect of a pre-exercise meal with different glycemic index (GI) on plasma IL-6 concentration and glucose metabolism during sub-max exercise (endurance performance run). Material : Ten men completed 1 h running at 70%-75% VO2max on a level treadmill on three occasions. In each trial, one of the three prescribed beverages as meal, i.e. high GI and low GL or placebo was consumed by the subjects 45 min before exercise. Blood samples were collected before, after, 1h and 24h after exercise. Result: Concentration of Plasma IL-6 in LGI group was less than HGI and Pla groups, IL-6 tended to significantly increase after exercise in groups (all P < 0.05), also there was significant difference for plasma IL-6 concentration between placebo and low glycemic groups in after exercise (P=.003) and 1hour after exercise (P=.005) . CK was significantly elevated at all- time points after exercise in 3 groups (all P < 0.05). Concentration of serum CK in LGI group was less than HGI and Pla groups but there not significantly. The consumption of the LGI beverage before exercise could minimize the increasing of plasma IL-6 concentration immediately after exercise and during the 1 h recovery period compared with the HGI beverage and Pla. Conclusion: This result suggested that the LGI beverage consumed as pre-exercise meal could modify the inflammatory response in prolonged exercise.